Whole-genome sequencing reveals genomic characterization of Listeria monocytogenes from food in China - Ji, Shunshi; Song, Zexuan; Luo, Lijuan; Wang, Yiqian; Li, Lingling; Mao, Pan; Ye, Changyun; Wang, Yan (Frontiers in Microbiology, 2023)
Introduction Listeria monocytogenes is a foodborne bacterium that could persist in food and food processing environments for a long time. Understanding the population structure and genomic characterization of foodborne L. monocytogenes is essential for the prevention and control of listeriosis. Methods A total of 322 foodborne L. monocytogenes isolates from 13 geographical locations and four food sources in China between 2000 and 2018 were selected for whole-genome sequencing. Results In silico subtyping divided the 322 isolates into five serogroups, 35 sequence types (STs), 26 clonal complexes (CCs) and four lineages. Serogroup IIa was the most prevalent serogroup and ST9 was the most prevalent ST of foodborne L. monocytogenes strains isolated in China. The in-depth phylogenetic analysis on CC9 revealed that ST122 clone might be original from ST9 clone. Furthermore, 23 potentially relevant clusters were identified by pair-wised whole-genome single nucleotide polymorphism analysis, indicating that persistent- and/or cross-contamination had occurred in markets in China. ST8 and ST121 were the second and third top STs of L. monocytogenes in China, which had heterogeneity with that of L. monocytogenes isolates from other countries. The antibiotic resistance genes aacA4, tetM, tetS, dfrG carried by different mobile elements were found in L. monocytogenes strains. One lineage II strain carrying Listeria Pathogenicity Island 3 was first reported. In addition, a novel type of premature stop codon in inlA gene was identified in this study. Discussion These findings revealed the genomic characteristics and evolutionary relationship of foodborne L. monocytogenes in China on a scale larger than previous studies, which further confirmed that whole-genome sequencing analysis would be a helpful tool for routine surveillance and source-tracing investigation.